Structural basis of broad protection against influenza virus by human antibodies targeting the neuraminidase active site via a recurring motif in CDR H3 - Gyunghee Jo; Seiya Yamayoshi; Krystal M. Ma; Olivia Swanson; Jonathan L. Torres; James A. Ferguson; Monica L. Fernández-Quintero; Jiachen Huang; Jeffrey Copps; Alesandra J. Rodriguez; Jon M. Steichen; Yoshihiro Kawaoka; et al. (Nature Communications)
Abstract Influenza viruses evolve rapidly, driving seasonal epidemics and posing global pandemic threats. While neuraminidase (NA) has emerged as a vaccine target, shared molecular features of NA antibody responses are still not well understood. Here, we describe cryo-electron microscopy structures of the broadly protective human antibody DA03E17, which was previously identified from an H1N1-infected donor, in complex with NA from A/H1N1, A/H3N2, and B/Victoria-lineage viruses. DA03E17 targets the highly conserved NA active site using its long CDR H3, which features a DR (Asp–Arg) motif that engages catalytic residues and mimics sialic acid interactions. We further demonstrate that this motif is conserved among several NA active site-targeting antibodies, indicating a common receptor mimicry strategy. We also identified BCR sequences containing this DR motif across all donors in a healthy human repertoire database, suggesting that such precursors may be relatively common and have vaccine targeting potential. Our findings reveal shared molecular features in NA active site-targeting antibodies that can be harnessed to design broad, immune-focused influenza vaccines.